2019
DOI: 10.3390/ma12071162
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the Effect of Air in Fluid Structure Interaction by Coupled SPH-FEM Methods

Abstract: Smoothed particle hydrodynamics (SPH) and the finite element method (FEM) are often combined with the scope to model the interaction between structures and the surrounding fluids (FSI). There is the case, for instance, of aircrafts crashing on water or speedboats slamming into waves. Due to the high computational complexity, the influence of air is often neglected, limiting the analysis to the interaction between structure and water. On the contrary, this work aims to specifically investigate the effect of air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Liang and Chen [31] applied the SPH-FEM method to soil-structure interaction problems during the seismic analysis of a rectangular underground structure, and results indicated that the distribution and magnitude of seismic earth pressure were influenced by the magnitude of soil deformation. Fragassa et al [32] analyzed the effect of air in FSI problems by coupling FEM and SPH. ey concluded that air had little effect on stress prediction, but it had a greater effect on the behaviour of the structure after the initial fluid impact.…”
Section: Introductionmentioning
confidence: 99%
“…Liang and Chen [31] applied the SPH-FEM method to soil-structure interaction problems during the seismic analysis of a rectangular underground structure, and results indicated that the distribution and magnitude of seismic earth pressure were influenced by the magnitude of soil deformation. Fragassa et al [32] analyzed the effect of air in FSI problems by coupling FEM and SPH. ey concluded that air had little effect on stress prediction, but it had a greater effect on the behaviour of the structure after the initial fluid impact.…”
Section: Introductionmentioning
confidence: 99%
“…are still vivid (alive) and up-to-date in the scientific discourse. Recent works on driven pile effects on nearby piles [17,18], and even a sophisticated analysis on the effect of "air in groundwater"-structure interaction [19] (during pile driving) confirms the necessity of developing knowledge on various aspects of this phenomena.…”
Section: Introductionmentioning
confidence: 95%
“…Figure 1 shows the generated 3D SPH-FEM model for pile punching, which consists of piles and soils. Symmetric modelling capabilities play an important role in numerical analysis to save the computational effort [26,27]. However, in certain cases, the symmetric boundary conditions cannot be applied due to the presence of non-symmetries in loading, material and boundary conditions [28].…”
Section: Establishment Of the 3d Sph-fem Model For Pile Punchingmentioning
confidence: 99%